Should, and how can, exercise be done during a coronavirus outbreak? An interview with Dr. Jeffrey A. Woods - Zhu, W. (Journal of Sport and Health Science, 2020)
Dr. Woods is a Mottier Family Professor at UIUC. His research focuses on the effects of exercise on the immune system, the gut microbiome, and aging. He was among the first scholars to demonstrate that regular exercise can have an anti-inflammatory effect on the body and showed that exercise can improve the immune response to the flu vaccine in older adults.